PEMIKIRAN HUKUM ISLAM ABU HANIFAH: Sebuah Kajian Sosio-Hostoris Seputar Hukum Keluarga - Juliansyahzen, M. Iqbal (Al-Mazaahib: Jurnal Perbandingan Hukum, 2015)
Abu Hanifah (80H-150H) is one of the figures who made valuable contributions to the development of Islamic law. His legal thought more advanced aspects of rationality that is affected by geographic and demographic environment of Iraq. Many progressive thinking and different from other scholars, both on methodological aspects and results of ijtihad. Islamic legal methodology of Abu Hanifah is istihsan, that caused controversy among scholars of fiqh. Many of Abu Hanifah’s thought in the area of family law that had different from others are: the permissibility of marriage without a guardian, the need kafaah in marriage, as well as nasab a child out of wedlock. Marriage without a guardian is valid, but not perfect. Abu Hanifah kafa'ah concept emerged as a response to social differences (social distinction) which then shifts into legal issues (legal distinction). Position child out of wedlock was fixed to his father as a legitimate child. In taking the law, Abu Hanifah tend to use Burhani epistemology. The dominance of the realm usage paradigm Burhani certainly can not be separated by geographical location or state of Abu Hanifah’s life. Kufa and Baghdad is a metropolitan city that Imam Abu Hanifa have to deal with high rationality.